WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG DI TAHURA Ir. H. DJUANDA - Rieke Sri Rizki; Nurani Nurani (Faculty of Economic and Business, University of Pasundan, 2019)
This study aims to determine the effect of word of mouth on tourist visiting decisions in Tahura Ir. H. Djuanda Bandung. The variables used are word of mouth and tourist visiting decisions. This research uses quantitative descriptive method verification by simple random sampling. through the distribution of questionnaires with the Differential Semantic scale with simple linear regression analysis. The sample is amounted to 100 respondents who were tourists visiting Tahura Ir. H. Djuanda Bandung. The results showed that the word of mouth variable, the smallest total score found in the dimensions of tracking (supervision) and the largest was at talking part (participation). For tourist visiting decision variables, the largest total score is the dimension of the number of visitors and the smallest, namely the payment method dimension, and the t test shows that there is a positive and significant influence between word of mouth on tourist visiting decision.